Simulation of ring interdigitated electrode for dielectrophoretic trapping - Mohd Mansor, Ahmad Fairuzabadi; Ibrahim, Siti Noorjannah (IEEE, 2016)
Electric field intensity is important in trapping biological cells during dielectrophoresis (DEP). In this paper, two designs of ring interdigitated electrode (RIDE) with varied spacing between electrodes; 300 µm to 500 µm, were modelled and analyzed. Analysis was done using finite element analysis software, COMSOL Multiphysics to study the intensities of electric fields generated on the electrodes. Simulation results show that higher electric fields are generated by the asymmetrical RIDE compared to the symmetrical RIDE design. The average value of positive electric fields peaks for symmetrical RIDE is 16.1kV/m and 19.9 kV/m for asymmetrical RIDE. Simulations also revealed that higher electric field were generated on smaller spacing compared to larger one. This suggested that better cellular attraction can be predicted on smallest distance of asymmetrical RIDE. Trapped cells can later be used to study the intercellular or intracellular interactions of the specific cells, such as through impedance sensing to form an integrated DEP-impedance biosensor.